ChemInform Abstract: Regioselective Synthesis of 1, 3‐ and 1, 2‐Tocopheryl Glyceride Ethers of Carboxylic Acids. Issue 23 (June 2015) - Choi, Bo Seul; Choi, Jeongae; Bak, Seonyoung; Koo, Sangho
Abstract Selective deprotection of 1, 2‐tocopheryl glyceride ethers (V) succeeds with Super‐Hydride, but the method suffers from a certain degree of acyl group migration even at low temperature and extremely short reaction time (formic acid quenching).